A consolidated review of commercial-scale high-value products from lignocellulosic biomass - Zheng, Bo; Yu, Shengzhu; Chen, Zhenya; Huo, Yi-Xin (Frontiers in Microbiology, 2022)
For decades, lignocellulosic biomass has been introduced to the public as the most important raw material for the environmentally and economically sustainable production of high-valued bioproducts by microorganisms. However, due to the strong recalcitrant structure, the lignocellulosic materials have major limitations to obtain fermentable sugars for transformation into value-added products, e.g., bioethanol, biobutanol, biohydrogen, etc. In this review, we analyzed the recent trends in bioenergy production from pretreated lignocellulose, with special attention to the new strategies for overcoming pretreatment barriers. In addition, persistent challenges in developing for low-cost advanced processing technologies are also pointed out, illustrating new approaches for addressing the global energy crisis and climate change caused by the use of fossil fuels. The insights given in this study will enable a better understanding of current processes and facilitate further development on lignocellulosic bioenergy production.